Investment and business climate of African countries in the field of energy - D. A. Pankov; O. V. Baykova (Вестник университета, 2025)
Investment and business climate of African countries in the field of energy depends on a number of factors, such as economic stability, natural resources, government support for business, and international partnerships. The relevance of the article is due to the fact that Africa has significant reserves of natural resources, and many states have great potential in the field of renewable energy sources, which makes the continent attractive for long-term investments. The purpose of this article is to identify the countries with the greatest potential in the sphere of natural resources and renewable energy, which are currently developing investment projects in the field of energy and at the same time have a favourable investment and business climate. The work evaluates the investment climate of African states based on the Moody’s rating agency, identifies the leading and outsider countries. The main investment projects currently being implemented in the field of energy in Africa are given. The analysis of the business climate of these states is conducted, the main problems, such as limited energy networks, poor development of transport infrastructure, political instability, and underdeveloped legal framework, are presented. As a result of the comparative analysis, it is revealed that despite the difficulties, the investment climate in a number of African countries in the field of energy has prospects for improvement due to such factors as the use of new technologies and creation of international partnerships. African countries that are actively implementing reforms and attracting foreign capital have the greatest prospects for developing the energy sector and improving the quality of life of the population.